2018
DOI: 10.1002/jbm.b.34091
|View full text |Cite
|
Sign up to set email alerts
|

Novel calcitonin gene‐related peptide/chitosan‐strontium‐calcium phosphate cement: Enhanced proliferation of human umbilical vein endothelial cells in vitro

Abstract: Bone cement materials have some disadvantages, including slow degradation and no biological activity, which greatly weakens their clinical application. Therefore, the search for a multifunctional bioactive bone cement has become urgent. In this study, a novel bone cement sample of calcitonin gene-related peptide (CGRP)/chitosan-strontium (Sr)-calcium phosphate cement (CPC) was developed. The structure and morphology were observed by scanning electron microscope (SEM). The cytotoxicity and proliferation of CGRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The addition of chitosan may be beneficial for anti‐washout. Aqueous solutions of chitosan are high in viscosity, and the viscosity will be increased by the cross‐linking of citric acid, which enhances the anti‐washed of the specimen 34,35 . Moreover, the cements also showed good injectability, indicating that the materials were beneficial for minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of chitosan may be beneficial for anti‐washout. Aqueous solutions of chitosan are high in viscosity, and the viscosity will be increased by the cross‐linking of citric acid, which enhances the anti‐washed of the specimen 34,35 . Moreover, the cements also showed good injectability, indicating that the materials were beneficial for minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, novel calcitonin gene-related peptide/chitosan-strontium-calcium phosphate cement enhances the proliferation of HUVECs (41). Furthermore, increasing extracellular Ca 2+ significantly triggers TNF-α-induced vascular cell adhesion molecule 1 activation and monocyte adhesion in HUVECs (42). Several reports have revealed that the p38 MAPK inhibitor (CBS3830) restricts vascular re-modeling in arterialized vein grafts (35).…”
Section: Discussionmentioning
confidence: 99%
“…Rat osteosarcoma cells, bone stromal cells, and chondrocytes attached well to RGD–chitosan and promoted mineralization [ 33 , 53 , 59 ]. Further, Lv et al reported that calcitonin gene-related peptide/chitosan containing cement promoted VEGF (vascular endothelial growth factor) mRNA expression and HUVEC (human umbilical vein endothelial cell) proliferation by controlling the release of the calcitonin gene-related peptide [ 60 ], and SIKVAV–chitosan hydrogels accelerated the re-epithelization of wounds and promoted angiogenesis in vivo [ 61 ].…”
Section: Properties Of Peptide–chitosan Matricesmentioning
confidence: 99%